Fructose addition to a glucose supplement modifies perceived exertion during strength and endurance exercise - da Silva-Grigoletto, M. E.; Fernández, J. M.; de Sá, C. A.; Gomez-Puerto, J. R.; Vaamonde, D.; Pérez-Jiménez, F. (The Journal of Strength and Conditioning Research, 2010)
The addition of fructose (F) to a glucose (G) supplement may modify the metabolic response during exercise; however, its effect on perceived exertion (PE) and its influence on postprandial metabolism have not been jointly studied in different types of exercise. This study sought to assess the acute effects of F addition to a G supplement on PE and on the postprandial metabolic response during a single bout of either strength exercise (SE) or endurance exercise (EE). Twenty physically trained men ingested an oral dose of G or GF 15 minutes before starting a 30-minute session of SE (10 sets of 10 repetitions of half squat) or EE (cycling). The combination resulted in 4 randomized interventions in a crossover design in which all subjects performed all experimental conditions: G + SE, GF + SE, G + EE, and GF + SE. Perceived exertion, heart rate (HR), G, insulin, lactate, and urinary catecholamine levels were measured before exercise, during the exercise, and during acute recovery. Perceived exertion during exercise was lower for GF than for G during SE and EE (mean ± SD; 8.95 ± 0.62 vs. 9.26 ± 0.65, p < 0.05 and 7.47 ± 0.84 vs. 7.74 ± 0.93, p < 0.05, respectively). The glycemic peak in GF + SE was lower than in G + SE (p < 0.05), and there was a second peak during recovery (p < 0.05), whereas in EE, no difference in blood G levels was noted between G and GF supplements. Moreover, HR, urinary adrenalin, and noradrenalin were lower in GF than in G (p < 0.05), though only for EE. The results showed that PE is positively affected by GF supplementation for both SE and EE and thus may be a useful dietary strategy for helping to achieve higher training loads.